2019
DOI: 10.1111/1750-3841.14911
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Preparation of Maillard Reaction Intermediate from Glutathione and Xylose and its Volatile Formation During Thermal Treatment

Abstract: Maillard reaction intermediate (MGX) generated from glutathione and xylose in aqueous medium was prepared via the Maillard reaction performed under a two-stage temperature increase process. The purified MGX was identified by Fourier-transform infrared spectroscopy, mass spectrometry, and nuclear magnetic resonance as N-(1-deoxyd-xylulos-1-yl)-glutathione (Amadori compound, C 15 H 25 O 10 N 3 S) with five main isomers. The method of Maillard reaction performed under a two-stage temperature increase process was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The calculated mass and measured mass of the RG-ARP in the positive mode were 440. 1333 12 The proposed molecular formula of the RG-ARP was C 15 H 25 O 10 N 3 S with a molecular mass of 439 Da by Mass Lynx software analysis (Figure 1a−c).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated mass and measured mass of the RG-ARP in the positive mode were 440. 1333 12 The proposed molecular formula of the RG-ARP was C 15 H 25 O 10 N 3 S with a molecular mass of 439 Da by Mass Lynx software analysis (Figure 1a−c).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…However, the varieties of flavor compounds derived from ARPs were far less than those from MRPs, which might be due to the asynchronous generation of recovered amino acids and α-dicarbonyl compounds from ARPs, and then limited the occurrence of Strecker degradation. 12,13 Some studies have shown that pyrazines could not be formed due to the release of recovered amino acids prior to α-dicarbonyl compounds in the ARP-only model, while the extra-added amino acids can compensate for the asynchrony and enhance the generation of pyrazines through Strecker degradation. 17,18 For the thermal processing of amino acid-derived ARPs, the influence of extra-added amino acids has been investigated and various improvements have been found for the formation of nitrogen-containing volatile compounds through Strecker degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The concentrations of products derived from ARPs were found much higher than those from complete MRPs . When glutathione and xylose were used as raw materials for the preparation of ARPs and MRPs, respectively, it was found that ARPs could generate volatile flavor compounds more quickly during the heat treatment, and some new compounds such as 2-methyl-5-methylthio-furan and 2-furanmethanethiol could be formed compared to MRPs . These results confirmed the superior capacity of ARPs in aroma formation.…”
Section: Introductionmentioning
confidence: 54%
“…The glutathione-glucose system produced less roasted and nutty aroma with the same quantity as the glutamic acid-cysteine-glycine-glucose system, resulting from a slower release of hydrogen sulfide and ammonia participating in the subsequent volatile formation [ 70 ]. Glutathione-xylose-ARP was produced with a high yield of 67.98% by simultaneous dehydration reaction and produced more ketones, alcohols, and mainly furans (caramel-like and sweet flavor) than the mixture of the ARPs of the three amino acid constituents [ 30 , 71 ]. Additionally, the glutathione-xylose-ARP produced a few sulfur-containing compounds while the mixture of cysteine-xylose-ARP and three amino acid ARP mixture generated a potent meaty flavor, supporting the aforementioned suggestions that cysteine-xylose-ARP is capable of forming meaty flavors and the process is strengthened by glycine addition, possibly split from glycine-xylose-ARP.…”
Section: Flavor Generationmentioning
confidence: 99%
“…HCAs are associated with tumor formation and cancers (breast, lung, stomach, and colon) in animal and human studies. [ 71 ] Formed by asparagine and reducing sugar, AA is linked with tumor formation and neurotoxic damage in animal studies [ 73 ]. Dietary consumption is mainly from Maillard-derived foods like fried potato, bakery, cereals, and coffee.…”
Section: Toxicologymentioning
confidence: 99%